EXPERIENCES THE INTERNATIONAL COMMUNITY SERVICE PROGRAM IN ANALYZING AND OVERCOMING BULLYING IN ELEMENTARY SCHOOL ENVIRONMENTS - Dewi Nazilatul Maghfirah; Anjar Kusuma Rahayu; Alnaria Maulida Intan Safitri; Agus Afandi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The issue of bullying in Indonesian elementary schools abroad is a recurring problem, even though students have received warnings and advice from teachers. This condition indicates the need for a more comprehensive approach to support the creation of a safe and child-friendly learning environment. Community service activities through this International KKN program aim to describe students' experiences in analyzing forms of bullying that arise and implementing intervention strategies suitable for the needs of partner schools. The implementation methods include observing student interactions, discussions with teachers, educational interventions through anti-bullying video screenings, providing daily advice, and routine reinforcement through video viewing during afternoon classes or religious study classes. The results show that the forms of bullying that appear include mockery regarding family conditions, reading abilities, religious differences, and even demanding money from younger students. Although video presentations have not been able to directly change behaviour, the combination of daily advice, habituation of values, and calling out students when violations occur has been able to reduce the frequency of bullying by about 60%. Discussions show that changes in student behaviour are gradual and require a repetitive process for empathy and mutual respect values to be internalized. This activity concludes that handling bullying requires a layered and consistent strategy to create more lasting change. Follow-up is recommended through continuous character habituation, parental involvement, and the development of long-term anti-bullying programs by the school.